Analysis of student questions in MOOC physics lectures: The case of the Khan Academy - Jeong, S; Song, J; Park, W (Korean Physical Society, 2019)
This study reports an analysis of 5,538 questions asked by learners after studying the classical physics and the quantum physics units in Khan Academy's physics course, a massive open online course (MOOC) platform popular worldwide. Based on Etkina’s and Harper et al.’s categories, the questions were coded into four levels of difficulty and six topics. In addition, the questions were further analyzed using semantic network analyses. In terms of the level of difficulty, classical physics showed similar numbers of high- and medium-level questions while in quantum physics, the number of high-level questions was significantly higher. In terms of the topic of the question, conceptual questions were the most frequently raised questions both in classical physics and quantum physics. In classical physics, questions about “concept” and “knowing” were frequently raised while the frequency of “concept” questions was significantly higher in quantum physics. The massive questions recorded on the MOOC platform allowed for effective analyses of physics questions by students. Educational implications and a prospective research agenda are proposed based on the findings.